Novel Opioids: Systematic Web Crawling Within the e-Psychonauts’ Scenario - Arillotta, Davide; Schifano, Fabrizio; Napoletano, Flavia; Zangani, Caroline; Gilgar, Liam; Guirguis, Amira; Corkery, John Martin; Aguglia, Eugenio; Vento, Alessandro (Frontiers in Neuroscience, 2020)
Background A wide range of novel psychoactive substances (NPSs) are regularly searched and discussed online by e-psychonauts. Among NPSs, the range of prescription/non-prescription opioids (fentanyl and non-fentanyl analogs) and herbal derivatives currently represents a challenge for governments and clinicians. Methods Using a web crawler (i.e., NPS.Finder®), the present study aimed at assessing psychonaut fora/platforms to better understand the online situation regarding opioids. Results The open-web crawling/navigating software identified some 426 opioids, including 234 fentanyl analogs. Of these, 176 substances (162 were very potent fentanyls, including two ohmefentanyl and seven carfentanyl analogs) were not listed in either international or European NPS databases. Conclusion A web crawling approach helped in identifying a large number, indeed higher than that listed by European/international agencies, of unknown opioids likely to possess a significant misuse potential. Most of these novel/emerging substances are still relatively unknown. This is a reason of concern; each of these analogs potentially presents with different toxicodynamic profiles, and there is a lack of docking, preclinical, and clinical observations. Strengthening multidisciplinary collaboration between clinicians and bioinformatics may prove useful in better assessing public health risks associated with opioids.